2007
DOI: 10.1038/sj.npp.1301404
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of D2-like Receptor Occupancy by Dopamine in the Putamen of Hemiparkinsonian Monkeys

Abstract: To advance understanding of the neurochemical changes in Parkinson's disease (PD), we compared D2-like dopamine receptor occupancy by dopamine in the control and lesioned putamen of four pig-tailed macaques treated unilaterally with MPTP. PET and in vitro binding techniques were used to measure binding potential (BP*) and density of D2-like dopamine receptors (B max ), respectively. As would be expected in PD, relatively higher values of BP* and B max and less amphetamine-induced decrease in [11 C]raclopride b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Earlier studies in monkeys and other species also suggested that D2LR binding in the pallidum and SNr does not change significantly with MPTP treatment Gnanalingham et al 1993;Hurley et al 1996), contrasting with the evidence that striatal expression of mRNA levels for D2LRs, presumably in medium spiny neurons, is increased in dopamine-depleted monkeys (Chefer et al 2008;Herrero et al 1996;Morissette et al 1996). Given that these neurons project predominately to GPe, one could expect an increased expression of D2 receptor immunoreactivity along striatopallidal axons and terminals.…”
Section: Effects Of Extrastriatal D2lr Activation In the Parkinsonianmentioning
confidence: 84%
“…Earlier studies in monkeys and other species also suggested that D2LR binding in the pallidum and SNr does not change significantly with MPTP treatment Gnanalingham et al 1993;Hurley et al 1996), contrasting with the evidence that striatal expression of mRNA levels for D2LRs, presumably in medium spiny neurons, is increased in dopamine-depleted monkeys (Chefer et al 2008;Herrero et al 1996;Morissette et al 1996). Given that these neurons project predominately to GPe, one could expect an increased expression of D2 receptor immunoreactivity along striatopallidal axons and terminals.…”
Section: Effects Of Extrastriatal D2lr Activation In the Parkinsonianmentioning
confidence: 84%
“… 53 , 54 For instance, positron emission tomography using [ 11 C]raclopride has shown an increased density of D 2 -class receptors in the putamen nucleus in PD. 55 Also, biochemical, electrophysiological, and behavioral data have shown that DA depletion increases the sensitivity (supersensitivity) of D 2 -class receptors in animals models of PD (e.g., DA depletion induced by reserpine, 56 α-methyl- p -tyrosine, 57 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine [MPTP], 58 and 6-hydroxydopamine [6-OHDA]). 49 , 59 , 60 In the 6-OHDA model, electrophysiological recordings in striatal MSNs have shown that D 3 R signaling contributes to the D 2 -class supersensitivity, 43 , 49 thus suggesting that DA depletion may increase D 3 R expression and activity.…”
Section: R Signaling In Brain Diseasesmentioning
confidence: 99%
“…Given the selectivity of [ 11 C]-(+)-PHNO for the D high 2 receptor (i.e. : unlike [ 11 C]raclopride which binds to both the DA receptor in high-and low-affinity states) (Seeman et al, 1993), an alternative explanation is that decreased Chefer et al, 2008) or in vivo (Cumming et al, 2003) is sustained by many in vitro studies, it is unclear whether this state of the receptor can actually be measured in vivo (Sibley et al, 1983;McCormick et al, 2008).…”
Section: Opposing Changes In [ 11 C]raclopride and [ 11 C]-(+)-phno Bmentioning
confidence: 99%